REVIEW TENTANG DESIGN MONETARY POLICY RULE UNTUK INDONESIA - Budhiasa, G. Sujana (Fakultas Ekonomi, UIN Maliki Malang, 2008)
The development monetary policy rule has become a fashionable macroeconomic modeling as pioneering by Taylor (1993) Indonesia is one of emerging market countries that has advantages in adopting the Taylor monetary policy rule that was implementing together with inflation targeting framework dealing with the central bank law of Bank Indonesia on the new task for stabilizing the domestic currency, so that the new law of Bank Indonesia might be appropriate to adopt inflation targeting framework (Taylor, 2000). According to the new law, Bank Indonesia is obliged to announce the inflation plan at the beginning of the year to the public. Alamsyah, Agung and Zulverdy (2001), point-out that Bank Indonesia has become implemented the inflation targeting framework because it was obligated by the new law of Bank Indonesia. Practical of inflation targeting framework (ITF) in many countries adopted Taylor modified monetary policy rules with using many anchors. Svensson (1999) argued that because uncertain of some economic variables behavior, using interest rate as single anchor as recommended by Taylor rules can be robustness.Bank Indonesia have practical a single anchor called SBI Rate in implementing the inflation targeting framework. SBI Rate is recommended by McNelis (1999) and also Darsono et. al (2002) as the single instrument rule for managing inflation gap and output gap in Indonesia.This paper is intends to study the development of policy rule theory and its possibility of those model developed for implementing at Bank Indonesia macroeconomic model.